Challenging Universalism: Contesting Global Gender Equality through Uang Japuik - Ningsih, Sherly Tricia (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2025)
This article investigates the Minangkabau matrilineal practice of uang japuik as a site of contestation against universalist international gender norms. Through a qualitative approach combining a literature review with discourse analysis of legal and cultural texts, this study employs norm contestation theory and postcolonial feminism to unpack the tensions between global values and local meanings. Findings show that uang japuik, a payment from the bride's family to the groom's, defies reduction to female commodification. Locally, it functions as a symbol of respect, reciprocity, and kinship, representing a distinct matrilineal logic of gender equality. The practice constitutes an epistemic resistance against global narratives that monolithically condemn marriage payments without cultural context. Ultimately, this research argues that the diffusion of international norms is a complex arena of negotiation, demanding a more pluralistic and culturally sensitive approach to the diverse pathways of women's emancipation in the Global South.